PERAN PEMERINTAH THAILAND DALAM MENANGGULANGI EKSPLOITASI SEKSUAL KOMERSIAL ANAK DI THAILAND - Widhi, Maulida Nila Cahyaning; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Tourism in Thailand has become a special attraction for local and foreign tourists to visit Thailand, especially for the purpose of sex tourism. The large number of sex tourists for sex tourism in Thailand is growing. Many children in Thailand who become child labor especially become Commercial Sex Workers (CSWs). One of reason why this happened caused by the development of tourism sector in Thailand. Children who work as prostitutes are one form of Commercial Sexual Exploitation of Children (CSEC). CSEC is one of the transnational crimes in which the crime of CSEC can be done in one country or more. This study aims to find out what is done by the government and the impact experienced by victims. The results obtained in this study are the Government of Thailand to make Child Protection Act and Anti-Trafficking in Person Act as one of the real forms of child conversion.